FEATURES OF ELECTRO- AND ECHOCARDIOGRAPHIC MANIFESTATIONS OF LEFT VENTRICULAR HYPERTROPHY, AGE ASPECTS - Акентьев, Сергей; Кулачек, Вероника; Тащук, Виктор; Руснак, Илона; Кулачек, Ярослав (SWorldJournal, 2021)
In order to determine the features of electro- and echocardiographic criteria for left ventricular hypertrophy (LVH) examined 202 patients with coronary heart disease was observed in 164 (81.19%) patients, and hypertension, among which 156 (77.23%) cases